‘Lifting the Veil’: The Challenges Posed by 2 Corinthians 3 - Stegman, S.J., Thomas D (Studies in Christian-Jewish Relations, 2011)
Second Corinthians 3 is a challenging text for Jewish-Christian relations. On the one hand, Paul sets forth there materials cherished by Christians, such as a beautiful description of the effect of the outpouring of God’s Spirit. On the other hand, he offers several derogatory remarks about the Mosaic covenant and his Jewish contemporaries who did not accept the gospel. This article argues that 2 Corinthians 3 is largely the product of Paul’s defensiveness. While it sets forth his positive teachings, the article also flags problematic materials. It concludes with remarks about how to appropriate this text today.